PENGARUH INTENSITAS AERASI TERHADAP PERTUMBUHAN DAN EFISIENSI PEMANFAATAN PAKAN BENIH IKAN GURAME (OSPHRONEMUS GORAMY): The Effect of Aeration Intensity on the Growth and Feed Utilization Efficiency of Giant Gourami (Osphronemus goramy) Fingerlings - Dini Safira; Hamid Hamid; Aminullah Aminullah (Yayasan Al-Amin Qalbu, 2026)
Giant gourami (Osphronemus goramy) is one of the most economically important freshwater fish species widely cultured in Indonesia. The success of giant gourami culture is strongly influenced by water quality, particularly dissolved oxygen availability, which can be improved through aeration. This study aimed to analyze the effect of aeration intensity on the growth and feed utilization efficiency of giant gourami (Osphronemus goramy) juveniles. The research was conducted from March to April 2026 at the Wet Laboratory, Faculty of Fisheries, Universitas 45 Mataram. An experimental method with a Completely Randomized Design (CRD) was used, consisting of four treatments and three replications. The treatments included P0 (without aeration), P1 (one air stone), P2 (two air stones), and P3 (three air stones). The results showed that the highest absolute weight growth was obtained in treatment P3, reaching 0.80 g/day, while the lowest was observed in P0 at 0.65 g/day. The highest absolute length growth was also recorded in P3 at 0.23 cm/day, whereas the lowest was found in P0 at 0.14 cm/day. The best FCR value was obtained in treatment P1 with a value of 1.98, while the highest feed utilization efficiency (FUE) was also observed in P1 at 50.42%. ANOVA results indicated that different aeration intensities did not significantly affect (Sig. >0.05) either weight growth or length growth of giant gourami juveniles. Treatment P3 resulted in the best growth performance, while treatment P1 provided the most efficient feed utilization.